Influence of Study Stream on the Students’ Information-Seeking Behaviour (Indian Journal of Extension Education, 2023)
The study was conducted to find out the association between information-seeking behaviour and the stream of study (faculty) of postgraduate students. The study used a structured online questionnaire to collect the data during 2022. From a sample of 378 postgraduate students chosen at random from eight faculties (Arts, Science, Engineering &Technology, Law, Commerce, Education, Fine Arts and Social Science) at the University of Rajasthan, Jaipur. The findings revealed a significant association between the respondents’ stream of study (faculty) and their purpose of seeking information, frequency of using the library, the purposes of use of the library, time spent in the library, purpose-wise usage of the internet, information sources used, browsing of different e-resources, and extent of use of e-resources. All selected aspects were found to be affected by the stream of study of the students. This research can be utilized to better understand the psychology of students seeking knowledge. This research may also aid in improving the university’s information delivery system based on students’ information-seeking behaviour.